The Effectiveness Of The Reward And Punishment Method On Increasing Learning Interest And Passing Ability Under Class Xi Students Of Class XI Smk Negeri 1 Gabuswetan - suwandi, suwandi (Journal of World Science, 2022)
Observations on the implementation of the volleyball game learning process in several schools showed that many problems were found, the lack of mastery of volleyball game technical skills, it was necessary to be taught in depth about volleyball game techniques. In connection with this problem, especially Passing, students need to be taught various kinds of Passing. In accordance with its development, Passing in volleyball is divided into two types, namely: Lower Passing, and Upper Passing, but Lower Passing which has a high level of difficulty. In accordance with the learning objectives of PJOK students are required to master the lower passing movements of the lessons taught but in the end many students are not interested in lower level learning. One of the efforts to improve and increase students' interest in participating in low-level learning is the need for appropriate learning modifications, namely by using the reward and punishment learning. The subjects in this study were 34 students of class XI SMK N 1 Gabuswetan. The research procedure was carried out using cycles of action (recycling). Recycling in research begins with planning (Planning), action (Action), observing (Observation), and reflecting (Reflection), and so on until the expected improvement is achieved. Based on the results of the study, it was found that there was an increase in student interest and learning outcomes. Before the application (Pre-Cycle) the average student interest in learning was 35% in the good category. In Cycle I, the average interest in learning volleyball lessons at the bottom increased where students' interest in learning rose to 53% in the fairly good category. In Cycle II, the average student interest in learning increased to 100% in the very good category (SB). In addition, there is an increase in students' ability to participate in lower level learning in volleyball lessons. At the pre-cycle stage, the frequency of the category is quite good, while in the first and second cycles, after applying the reward and punishment learning model, the results are in the good category.